Mechanism of digital economy on carbon emissions: based on the perspective of green finance development - Zhang, Xiaoyun; Rong, Jia (Frontiers in Environmental Science, 2025)
Carbon emissions are increasingly becoming a focal point of green policies and lifestyle choices. China’s “dual carbon” policy mandates the expansion of its digital economy to decrease carbon emissions. This study utilizes panel data from 30 Chinese provinces from 2011 to 2023 to investigate the influence of the digital economy on reducing carbon emissions through mediation and threshold effect models. The following conclusions have been made: The digital industry’s expansion hinders carbon emissions, leading to a progressive reduction in carbon emissions as the digital economy advances. The digital economy has a significant threshold effect on carbon emissions, showing a non-linear relationship between the impact of the digital economy on carbon emissions. By utilizing green finance as a mediating factor, the digital economy can address the issue of carbon emissions by improving the level of green finance development, thereby reducing regional carbon emissions. Geographical variations affect how the digital economy impacts carbon emissions, with varying degrees of influence across different locations. To achieve the “dual carbon” development goals, it is essential to carefully analyse the digital economy’s impact on reducing carbon emissions, enhancing the theoretical framework for environmental pollution management, and maximizing the digital economy’s capabilities.